A national survey on current use of mycophenolate mofetil for childhood-onset systemic lupus erythematosus in Japan. Issue 6 (8th September 2015) - Hara, Ryoki; Miyazawa, Hirotaka; Nishimura, Kenichi; Momoi, Takahiro; Nozawa, Tomo; Kikuchi, Masako; Sakurai, Nodoka; Kizawa, Toshitaka; Shimamura, Sanae; Yasuda, Shinsuke; Hiromura, Keiju; Sada, Ken-ei; et al.
Abstract : Purpose. To conduct a national survey of systemic lupus erythematosus (SLE) patients treated with mycophenolate mofetil (MMF). Based on current information on the use of MMF, we aimed to evaluate its efficacy and safety for childhood-onset (c-) SLE. Target. We evaluated 115 patients by questionnaire on MMF use for c-SLE in medical facilities specializing in pediatric rheumatic and renal diseases. Results. Average age at SLE onset was 10.6 (range, 2–15) years; average age at the time of starting MMF was 12.3 (range, 2–15) years. Average dose per body surface area was 1, 059.3 mg/m 2 /day. Corticosteroid dosing was 20.9 mg/day before treatment but 7.7 mg/day after treatment. Laboratory values before and after MMF treatment were as follows: C3 increased from 67.0 to 84.9 mg/dl ( p < 0.001), C4 increased from 10.2 to 15.1 mg/dl ( p < 0.001), and anti-DNA antibody decreased from 154.2 to 18.4 IU/ml ( p < 0.001). 24 adverse events in 21 cases were reported, but MMF was not discontinued in any. Conclusions. The amount of MMF for c-SLE in Japan is similar to the standard dose in other countries. Reduction of corticosteroid dose and improvement of laboratory values represent efficacy of MMF. The side effects recorded here indicated tolerability of the drug.